1999
DOI: 10.1029/1998ja900026
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of magnetospheric waveguide modes by magnetosheath flows

Abstract: Abs[rac[. Standard models of the Earth's outer magnetospheric waveguide assume that a perfectly reflecting magnetopause can trap energy inside the waveguide. In contrast, we show that the near-noon magnetopause often acts as a leaky boundary, wave trapping only being possible for large magnetosheath flow speeds. Moreover, for sufficiently fast flow speeds, we show how waveguide modes may be energized by magnetosheath flows via the overreflection mechanism. Unbounded simulations of the growth of surface waves v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
238
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(259 citation statements)
references
References 53 publications
(50 reference statements)
19
238
0
2
Order By: Relevance
“…It was observed that, at auroral latitudes, low-frequency pulsations show a clear morning/afternoon asymmetry, with an higher occurrence rate in the morning (Rostoker and Sullivan, 1987;Ziesolleck and McDiarmid, 1995;Chisham and Orr, 1997;Mathie et al, 1999) and that afternoon pulsations are driven dominantly by sporadic impulses in the SW (Rostoker and Sullivan, 1987). Consistent with the theory by Mann et al (1999), who investigated the energization of waveguide modes by magnetosheath flows on the magnetopause flanks, and with the observations by Mathie et al (1999) and Matthie and Mann (2000), the observed morning/afternoon asymmetry can be explained in terms of a greater stability of the postnoon magnetopause to shear-flow instabilities than the dawn flank; in this sense, pulsations driven by magnetopause instabilities during intervals of enhanced SW speed occur predominantly in the morning, while impulsively driven pulsations may extend over a wide range of local times. It is interesting to note that at low latitude, the occurrence of pulsations at cavity/waveguide mode frequencies is statistically higher in the afternoon (Villante et al, 2001); this feature has been interpreted in terms of SW pressure pulses associated with corotating structures, which more frequently impinge on the postnoon magnetopause.…”
Section: Introductionsupporting
confidence: 75%
“…It was observed that, at auroral latitudes, low-frequency pulsations show a clear morning/afternoon asymmetry, with an higher occurrence rate in the morning (Rostoker and Sullivan, 1987;Ziesolleck and McDiarmid, 1995;Chisham and Orr, 1997;Mathie et al, 1999) and that afternoon pulsations are driven dominantly by sporadic impulses in the SW (Rostoker and Sullivan, 1987). Consistent with the theory by Mann et al (1999), who investigated the energization of waveguide modes by magnetosheath flows on the magnetopause flanks, and with the observations by Mathie et al (1999) and Matthie and Mann (2000), the observed morning/afternoon asymmetry can be explained in terms of a greater stability of the postnoon magnetopause to shear-flow instabilities than the dawn flank; in this sense, pulsations driven by magnetopause instabilities during intervals of enhanced SW speed occur predominantly in the morning, while impulsively driven pulsations may extend over a wide range of local times. It is interesting to note that at low latitude, the occurrence of pulsations at cavity/waveguide mode frequencies is statistically higher in the afternoon (Villante et al, 2001); this feature has been interpreted in terms of SW pressure pulses associated with corotating structures, which more frequently impinge on the postnoon magnetopause.…”
Section: Introductionsupporting
confidence: 75%
“…Moreover, Rostoker and Sullivan (1987) reported that a large fraction of the afternoon pulsations they observed were perhaps driven by impulses in the solar wind rather than the magnetopause instabilities thought to energize the morning sector pulsations. In a survey of Pc 5 pulsation events observed with the IMAGE array, Mathie et al (1999) presented evidence of clear resonance signatures in the morning sector, but showed that FLR signatures were ill-defined closer to local noon, consistent with the scenario described by Mann et al (1999).…”
Section: Introductionmentioning
confidence: 53%
“…Allan et al, 1986;Samson et al, 1992;Mann et al, 1999) or Kelvin-Helmholtz instability surface waves on the flanks of the magnetopause (e.g. Southwood, 1974;Fujita et al, 1996;Engebretson et al, 1998;Rae et al, 2005) have been proposed, the spatial amplitude and phase structures of ground based magnetic field measurements during FLR events are commonly accepted due to abundant experimental evidence (e.g.…”
Section: Introductionmentioning
confidence: 99%